2007
DOI: 10.5034/inquiryjrnl_44.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Length of Hospice Care among U.S. Adults: 1992–2000

Abstract: This study examined length of service use among U.S. adult hospice patients based on data from the 1992–2000 National Home and Hospice Care Surveys. With the Kaplan-Meier method, we estimated length of service use of current and discharged hospice patients simultaneously. Using a multivariate Cox proportional hazards model, we examined trends in patients' service use during the 1990s. Findings show that length of service use decreased significantly among adult patients who had Medicare as their only payment so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…Descriptive statistics for each race/ethnic group with number and percent in sub-groups for all predictor variables are shown in Table 3. Race/ethnicity, gender, and SES levels were assessed across percent of time for length of stay in hospice (7,, and >60 days) within the calendar years of NSCLC diagnosis (1991-1995, 1996-1999, 2000-2005) and AJCC stages I-II and III-IV (Table 1). In Tables 1 and 3, statistics were performed using Pearson's chi-square tests of hypothesis for independence; and statistical significance was assessed using a p-value of <0.05 as the cut-off point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Descriptive statistics for each race/ethnic group with number and percent in sub-groups for all predictor variables are shown in Table 3. Race/ethnicity, gender, and SES levels were assessed across percent of time for length of stay in hospice (7,, and >60 days) within the calendar years of NSCLC diagnosis (1991-1995, 1996-1999, 2000-2005) and AJCC stages I-II and III-IV (Table 1). In Tables 1 and 3, statistics were performed using Pearson's chi-square tests of hypothesis for independence; and statistical significance was assessed using a p-value of <0.05 as the cut-off point.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more blacks (60.1%) were unmarried at the time of hospice death, unlike Asians/Pacific Islanders (60.8%), who tended to be married. Percent length of stay in hospice care Table 1 presents the length of stay in hospice (7,, and >60 days) stratified by tumor stage (I-II and III-IV) and year of NSCLC diagnosis (1991-1995, 1996-1999, 2000-2005), and assessed across race/ethnicity, gender, and SES levels. Adjusted incidence rate ratios for length of stay in hospice Overall from 1991 to 2005, the IRR for length of stay in hospice was increased in females, over advancing age groups from 70 years, and from highest to poorest SES quartile for stages I-IV NSCLC.…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified a number of factors associated with shorter lengths of stay in hospice, including referral from a hospital 6–9 . Although referral to hospice from a hospital may reflect a patient's decision to transition from the use of life‐sustaining therapies to care focused on comfort, such referrals may also reflect poorer access to care or to information about hospice in settings outside of the hospital.…”
mentioning
confidence: 99%
“…Previous studies have identified a number of factors associated with shorter lengths of stay in hospice, including referral from a hospital. [6][7][8][9] Although referral to hospice from a hospital may reflect a patient's decision to transition from the use of life-sustaining therapies to care focused on comfort, such referrals may also reflect poorer access to care or to information about hospice in settings outside of the hospital. For example, because of fewer primary care visits and greater frequency of hospitalization in the last months of life, African Americans, a group historically underrepresented in hospice, may be more likely to be referred to hospice from hospitals.…”
mentioning
confidence: 99%